2012
DOI: 10.2139/ssrn.2200378
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Weight Loss, and Employment Prospects – Evidence from a Randomized Trial

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Recent work by Lindeboom et al. () and Caliendo and Lee () and experimental work by Reichert () has found that weight or weight loss among men does not affect the probability of gaining employment. Our results are consistent with this overall conclusion, but yield the additional insight that body weight does affect the particular kind of work an individual is likely to attain conditional on wage offers.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work by Lindeboom et al. () and Caliendo and Lee () and experimental work by Reichert () has found that weight or weight loss among men does not affect the probability of gaining employment. Our results are consistent with this overall conclusion, but yield the additional insight that body weight does affect the particular kind of work an individual is likely to attain conditional on wage offers.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study of the impact of weight on employment (Reichert, 2015) used a novel identification strategy: random assignment to a weight loss intervention that offered monetary rewards for weight loss, as opposed to assignment to a control group. The IV estimates suggest that a 1 percentage point reduction in BMI raises the probability of employment for women by 2.1 percentage points (2.8%) but has no impact on the employment probability of men.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that adults can be incentivized to go to the gym more often, but the effects are short-lived and people seem to find it difficult to change their habits permanently (DellaVigna and Malmendier, 2006;Royer et al, 2015;Carrera et al, 2018Carrera et al, , 2020. Exceptions are Reichert (2015) and Augurzky et al (2018) who find long(er)lasting effects on weight loss and health behavior in a randomized controlled trial among obese health plan enrollees in Germany. In one of the few studies that focuses on children, Angelucci et al (2020) study peer effects in health behaviors in a field experiment among K-8 school children in Chicago.…”
Section: Introductionmentioning
confidence: 99%